(untitled) (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: Tuberculosis is a highly infectious disease and has the highest burden with it. Diagnosis of tuberculosis in many countries is still dependent on microscopy. For developing countries with a large number of cases and financial constraints, evaluation of rapid and inexpensive diagnostic methods has great importance. Culture of Mycobacterium tuberculosis complex (MtbC) is the accepted reference standard for confirmation of TB infection and is necessary for drug susceptibility testing (DST). There are several methods for culturing MtbC using solid and liquid media. Although solid media has been used for over 100 years, liquid culture media is increasingly being introduced in low and middle income countries (LMIC). Objective: The purpose of the present study was to compare the efficacy of solid culture and liquid culture in the diagnosis of pulmonary tuberculosis. Methodology: This cross sectional study was done in the Department of Microbiology at Sir Salimullah Medical College, Dhaka and National Institute of Chest Disease & Hospital (NIDCH), Dhaka during the period of January 2016 to December 2016 for a period of 1(one) year. Sputum samples from suspected MDR-TB patients were collected by purposive sampling technique from OPD of Sir Salimullah Medical College (SSMC) and NIDCH. Microscopy, liquid culture in liquid MGIT 960 media were done for MTB diagnosis. Result: This study shows the comparison of results of microscopic examination of solid culture and liquid culture (MGIT 960). The liquid MGIT 960 method detected more positive samples than solid culture 68% vs 67%. The mean turnaround time of detection (TTD) of MTB was 34.3±5.2 days for Lowenstein-Jensen media and 17.5±3.8 days for MGIT 960 (p value <0.05). So, liquid culture gave earlier result than solid culture. Conclusion: Liquid culture more positive result than solid culture under microscope in smear of sputum and also liquid culture gave earlier result than solid culture. J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 28-31